Coenzyme Q10 redox state predicts the concentration of c‐reactive protein in a large caucasian cohort. (23rd February 2016) - Fischer, Alexandra; Onur, Simone; Niklowitz, Petra; Menke, Thomas; Laudes, Matthias; Döring, Frank
Abstract: In the present study the relationship between the CoQ10 redox state (% oxidized form of CoQ10 ) and the serum level of c‐reactive protein (CRP) was investigated in a large Caucasian study population ( n = 1319). In order to evaluate independently the influence of the variables that predict the outcome of CRP, an analysis of covariance (ANCOVA) was performed with CRP as the dependent variable. Gender was taken as an independent factor and CoQ10 redox and BMI as independent covariates. Results were substantiated with findings from a human intervention study ( n = 53), receiving 150 mg/day ubiquinol for 14 days. Spearman's correlation revealed a significant ( P < 0.001) association between the CoQ10 redox state and CRP concentrations in the whole study population. Thus, higher CRP concentrations were found in subjects having more oxidized CoQ10 . Similar results were evident for further inflammatory markers (interleukin‐6, number of leucocytes). The ANCOVA revealed a significant ( P < 0.001) prediction of CRP concentrations by CoQ10 redox state, after controlling for the effect of BMI and separately for gender. In the intervention study it was further found that the oral intake of ubiquinol increased its proportion significantly ( P < 0.001), with the highest increase in those persons having a low basal serum ubiquinol content (<92.3%). Here it was discovered that the ubiquinol status significantly correlated to the concentration of the inflammation marker monocyte chemotactic protein 1. It is concluded that CoQ10 redox state predicts the concentration of CRP. Persons at risk with lower ubiquinol status, higher BMI, and low grade inflammation may benefit from ubiquinol supplementation. © 2016 BioFactors, 42(3):268–276, 2016